Characterizations of polybenzoxazine modified with isomeric biphenyltetracarboxylic dianhydrides - B. Ramsiri; C. Jubsilp; I. Dueramae; S. Rimdusit (eXPRESS Polymer Letters, 2012)
A series of polymeric alloying films were prepared from bisphenol A/aniline-based bifunctional benzoxazine resin (BA-a) with three isomeric biphenyltetracarboxylic dianhydrides, i.e., 2,3,'3,4'-biphenyltetra carboxylic dianhydride (a-BPDA), 2,2',3,3'-biphenyltetracarboxylic dianhydride (i-BPDA), and 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA) through fully thermal curing. Chemical structure, thermomechanical property and thermal stability of bisphenol A/aniline type polybenzoxazine (PBA-a) copolymers were evaluated. Their chemical structures analyzed via Fourier transform infrared spectroscopy reveal ester carbonyl linkage formation between hydroxyl group of the PBA-a and anhydride group in the isomeric dianhydride. Glass transition temperatures (Tgs) of the dianhydride-modified PBA-a increased with PBA-a"<<"i-BPDA"<"a-BPDA"<"s-BPDA. Degradation temperatures (Td) of the PBA-a copolymers recorded to be in the range of 365–402°C were significantly higher than that of the neat PBA-a i.e. 334°C. Finally, char yield of the PBA-a copolymers was found to be about 54–57% which is about twofold increase from that of the parent PBA-a.